TRANSLOTOLOGICAL PROBLEMS OF HUMAN BEHAVIOURAL LEXEMES IN ENGLISH AND UZBEK LANGUAGES - Alimukhamedova Khabiba Rustamovna (Scholar Express Journal, 2022)
The main features of the cognitive and linguistic mechanisms of the formation of behavioural meanings and the literal formation of behaviour confirm that behaviour is manifested as a set of actions expressed by these actions and mental or emotional states and relationships behind them. This article gives information about translotological problems of human behavioural lexemes in English and Uzbek languages
Keywords: Human behaviour; humanities; feature; component